Impact and cost-effectiveness of formal gastroenterology outpatient referral Clinical Assessment Service. Issue 2 (23rd September 2017) - Pelitari, Stavroula; Hathaway, Charlotte; Gritton, Dean; Smith, Andrea; Bush, David; Menon, Shyam; McKaig, Brian
Abstract : Objective: The aim was to assess the financial and operational impact of our new gastroenterology referral pathway model on our services. Design: An electronic 'Clinical Assessment Service' (CAS) proforma and an information platform were developed, and all data were analysed retrospectively. Setting: Royal Wolverhampton NHS Trust. Patients: 14 245 general practitioner (GP) referrals were received during January 2014–December 2016 with 9773 of them being triaged via our CAS. Main outcome measures: We looked into patients' clinical outcome along with departmental performance and finances. Results: A new outpatient appointment was offered to 60.1% (n=5873) of the CAS referred patients. Endoscopic or radiological investigations were requested for 29.2% (n=2854) of patients prior to deciding on further management plan. Out of those, 27% (n=765) went on to receive another gastroenterology (GI) clinic appointment. The remaining 21.3% (n=2089) of the CAS patients were discharged back to their GP following initial investigations. 5.5% (n=538) were discharged back to primary care with a letter of advice, whereas 5.2% (n=509) were deemed inappropriate for GI clinic and were redirected to other specialists. Overall, 32% (n=3127) of patients were managed without a face to face consultation in the GI clinic. This corresponds to 3136 less outpatient appointments with estimated reduced expenditure by the Clinical Commissioning Group (CCG) of £481K. The 18-week performance and waiting times remained stable despite the increasing referral population. The DNA rate dropped from 14% pre to 8.5%. Conclusions: Our clinical assessment model has, in addition to the clinical benefits, a considerable positive financial impact to the health economy.